2002
DOI: 10.1007/s001220100761
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and chromosomal localisation of C-type low-molecular-weight glutenin subunits in the bread wheat cultivar Chinese Spring

Abstract: Low-molecular-weight glutenin subunits are classically divided into the B, C and D groups. Most attention has been paid to the characterisation of the B and D groups, whereas C subunits, although represented by a large number of protein components, have not been thoroughly characterised, mainly because they tend to separate with the gliadins in many fractionation procedures. Here we describe a procedure for obtaining a fraction strongly enriched in C subunits that has allowed us to determine the chromosomal lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…The LMW glutenins in the B group (40-50 kDa) are the most basic subunits, while the C-group subunits (30-40 kDa) have a wide range of pIs. It has been found by N-terminal amino sequencing that the C group of LMW glutenins contain up to 95% modified or mutant gliadins that have become incorporated into the polymer via disulfide bonding (Tao and Kasarda 1989;Lew et al 1992;Masci et al 2002). The D-group subunits are modified ω-gliadins (44-74 kDa) with at least one cysteine residue in their sequences, and they are the most acidic of all endosperm proteins (Masci et al 1991(Masci et al , 1993.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The LMW glutenins in the B group (40-50 kDa) are the most basic subunits, while the C-group subunits (30-40 kDa) have a wide range of pIs. It has been found by N-terminal amino sequencing that the C group of LMW glutenins contain up to 95% modified or mutant gliadins that have become incorporated into the polymer via disulfide bonding (Tao and Kasarda 1989;Lew et al 1992;Masci et al 2002). The D-group subunits are modified ω-gliadins (44-74 kDa) with at least one cysteine residue in their sequences, and they are the most acidic of all endosperm proteins (Masci et al 1991(Masci et al , 1993.…”
Section: Introductionmentioning
confidence: 96%
“…On the basis of N-terminal amino acid sequences, they can be divided into LMW-m, LMW-s, and LMW-i types (Kasarda et al 1988;Tao and Kasarda 1989;Lew et al 1992;Cloutier et al 2001). The LMW-s type have been found to be the predominant type by N-terminal sequencing of proteins and belongs to the B group of LMW glutenins (Lew et al 1992;Masci et al 2002). The LMWm type is the most predominant type found by gene sequencing and belong to both the B and C groups of LMW glutenins.…”
Section: Introductionmentioning
confidence: 97%
“…It could be a γ-gliadin type subunit, because previous studies showed that a major C subunit of Norin 61 was encoded by Glu-D3 containing a γ-gliadin-like Nterminal amino acid sequence 13 . Other studies 11,12 revealed that most of the LMW-GSs in the C subunits shared a similarity of amino acid sequences to those of α-and γ-gliadins that carry a single additional cysteine residue involved in the formation of an intermolecular disulfide bond. Therefore, this LMW-GS could be encoded by the Gli-D1 locus tightly linked to Glu-D3 locus.…”
Section: Fig 2 Pcr Analysis Of Glu-a3-specific Lmw-gs Genementioning
confidence: 85%
“…The number of repeats, ranging between about 12 and 25, in the repetitive domain is mainly responsible for its length variation. Although the allelic variation of LMW-GS has been widely characterized at the protein level in wheat and its relatives [5,6,[18][19][20], the research on the genetic variation of LMW-GS at DNA level is still lacking.…”
Section: Introductionmentioning
confidence: 99%